Tea consumption is associated with a reduced risk of high-altitude pulmonary hypertension among high-altitude permanent inhabitants in the Tibetan population: a case-control study - Tong, Wuyang; Cheng, Ran; Chen, Xiaoming; Zhang, Xuesen; Li, Wanmin; Luo, Xiaqing; Xu, Shipeng; Bi, Xianjin (Frontiers in Nutrition, 2026)
BackgroundThis study investigated the potential association between tea consumption and high-altitude pulmonary hypertension (HAPH) risk in a long-term, high-altitude Tibetan population, which remained unexplored.MethodsIn a hospital-based case-control study, 113 patients with HAPH and 113 controls were included. Data were collected from medical records and a tea consumption questionnaire. Group comparisons were performed using t-tests, Mann–Whitney U, Chi-square, or Fisher's exact test. Univariate and multivariable logistic regression analyses determined the tea–HAPH relationship (p < 0.05).ResultsPatients with HAPH exhibited significant right-heart structural alterations and a distinct metabolic profile characterized by lower lipid and glucose levels. A significant inverse association was observed between tea consumption and HAPH risk. Compared to the control group, patients with HAPH exhibited a significantly lower proportion of tea consumption (45.1% vs. 59.3%, p = 0.033). After adjusting for confounders, including age, hemodynamic, and metabolic parameters, regular tea consumption remained an independent protective factor (adjusted OR = 0.496, 95% CI: 0.258–0.952). Tibetan tea exhibited the strongest protective effect (adjusted OR = 0.300, 95% CI: 0.123–0.735). A significant dose-response relationship was observed, with the significant risk reduction at higher consumption frequency (≥6 days/week: adjusted OR = 0.208), more tea consumption (≥3 cups/day: adjusted OR = 0.305), and longer duration (≥20 years: adjusted OR = 0.210).ConclusionRegular Tibetan tea consumption significantly reduces HAPH risk in a dose-response manner. These findings offer new insights into dietary factors in HAPH etiology and can explain Tibetan adaptation to high altitudes.